Improvement of phonemic fluency following leftward prism adaptation - Patrizia Turriziani (Nature Portfolio, 2021)
Abstract Anatomo functional studies of prism adaptation (PA) have been shown to modulate a brain frontal-parieto-temporal network, increasing activation of this network in the hemisphere ipsilateral to the side of prism deviation. This effect raises the hypothesis that left prism adaptation, modulating frontal areas of the left hemisphere, could modify subjects’ performance on linguistic tasks that map on those areas. To test this hypothesis, 51 healthy subjects participated in experiments in which leftward or rightward prism adaptation were applied before the execution of a phonemic fluency task, i.e., a task with strict left hemispheric lateralization onto frontal areas. Results showed that leftward PA significantly increased the number of words produced whereas rightward PA did not significantly modulate phonemic fluency. The present findings document modulation of a language ability following prism adaptation. The results could have a huge clinical impact in neurological populations, opening new strategies of intervention for language and executive dysfunctions.